A survey of salmon gill poxvirus (SGPV) in wild salmonids in Norway. Issue 1 (26th July 2017) - Garseth, Å H; Gjessing, M C; Moldal, T; Gjevre, A G
Abstract: In 2016, the Norwegian health monitoring programme for wild salmonids conducted a real‐time PCR‐based screening for salmon gill poxvirus (SGPV) in anadromous Arctic char ( Salvelinus alpinus L.), anadromous and non‐anadromous Atlantic salmon ( Salmo salar L.) and trout ( Salmo trutta L.). SGPV was widely distributed in wild Atlantic salmon returning from marine migration. In addition, characteristic gill lesions, including apoptosis, were detected in this species. A low amount of SGPV DNA, as indicated by high Ct‐values, was detected in anadromous trout, but only in fish cohabiting with SGPV‐positive salmon. SGPV was not detected in trout and salmon from non‐anadromous water courses, and thus seems to be primarily linked to the marine environment. This could indicate that trout are not a natural host for the virus. SGPV was not detected in Arctic char but, due to a low sample size, these results are inconclusive. The use of freshwater from anadromous water sources may constitute a risk of introducing SGPV to aquaculture facilities. Moreover, SGPV‐infected Atlantic salmon farms will hold considerable potential for virus propagation and spillback to wild populations. This interaction should therefore be further investigated.